Generation and recombination of free-carriers in silicon nano-waveguides - Dainese, Paulo; Aldaya, Ivan [UNESP]; Gil-Molina, Andres; Gabrielli, Lucas H.; Fragnito, Hugo L.; Pita, Julian L.; Schroder, H.; Chen, R. T. (Spie-int Soc Optical Engineering, 2019)
Generation and recombination of free carriers in silicon photonics is fundamental to understand several nonlinear optical phenomena and engineer novel devices. Particularly in strip nano-waveguides, the tightly confined optical field results in highly efficient generation of free-carriers, both through linear and nonlinear absorption. Furthermore, the large surface-to-volume ratio results in a nonlinear recombination behavior dominated by a trap-assisted mechanism. Through time-resolved pump-and-probe experiments, we performed a detailed experimental characterization of linear and nonlinear generation rates, as well as recombination dynamics. We developed analytical expressions to determine the carrier density averaged along the waveguide from the measured free-carrier absorption for different input pump power levels. As a result, we were able to discriminate the contributions from two-photon absorption (TPA) and single-photon absorption (SPA), obtaining absorption coefficients of (1.5 +/- 0.1) cm/GW and (1.9 +/- 0.1) m(-1), respectively. Our results then reveal that the effective TPA within the waveguide is higher than the value reported for bulk silicon, and that SPA plays an important role in carrier generation up to R.:300 mW. With regards to recombination dynamics, our results show a highly nonlinear decay curve with instantaneous carrier lifetime varying as the recombination evolves (initially faster with lifetime of 800 ps and slower at final stages of the decay, reaching 300 ns). We interpret our results with a theoretical framework based on trap-assisted recombination statistics applied to strip nano-waveguides, and explore its implication to the dynamics of nonlinear nanophotonic devices in which free carriers play a critical role.
Keywords: Semiconductor; silicon photonics; two-photon absorption; free-carrier generation; free-carrier recombination